Construction of artificial periosteum with methacrylamide gelatin hydrogel-wharton's jelly based on stem cell recruitment and its application in bone tissue engineering - Wentao Zhang; Tianze Sun; Jing Zhang; Xiantong Hu; Ming Yang; Liwei Han; Gang Xu; Yantao Zhao; Zhonghai Li (Materials Today Bio, 2023)
The presence of periosteum can greatly affect the repair of a bone fracture. An artificial periosteum imitates the biological function of natural periosteum, which is capable of protecting and maintaining bone tissue structure and promoting bone repair. In our artificial periosteum, biocompatible methacrylate gelatin was used to provide the mechanical support of the membrane, E7 peptide added bioactivity, and Wharton's jelly provided the biological activity support of the membrane, resulting in a hydrogel membrane (G-E-W) for the chemotactic recruitment of bone marrow mesenchymal stem cells (BMSCs) and promoting cell proliferation and osteogenic differentiation. In an in vitro experiment, the G-E-W membrane recruited BMSCs and promoted cell proliferation and osteogenic differentiation. After 4 weeks and 8 weeks of implantation in a rat skull defect, the group implanted with a G-E-W membrane was superior to the blank control group and single-component membrane group in both quantity and quality of new bone. The artificial G-E-W membrane recruits BMSC chemotaxis and promotes cell proliferation and osteogenic differentiation, thereby effectively improving the repair efficiency of fractures and bone defects.